(untitled) (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
This study aims to analyze the interest of students in Gresik City in using digital investment, particularly cryptocurrency, as an alternative investment instrument. The research employs a quantitative approach with data collected through questionnaires distributed to students in Gresik City. The sampling method used was purposive sampling, with a total of 100 respondents. Data analysis was carried out using multiple linear regression with the help of SPSS software. The results show that Social Influence and Facilitating Conditions have a positive and significant effect on students’ interest in cryptocurrency investment. Meanwhile, Performance Expectancy and Effort Expectancy do not have a significant effect. Simultaneously, the four independent variables significantly influence students’ investment interest. These findings indicate that social encouragement and the availability of supporting facilities are the main factors driving students to invest in cryptocurrency, while perceived benefits and ease of use are not considered decisive factors.